Halal foods in the global retail industry - Raja Yusof, Raja Nerina (Universiti Putra Malaysia Press, 2013)
Focusing on Islam, this book is illustrating how the practices in Islam, in this case the halal and haram standards in consumption behavior of Muslims, can be used by adapting global retailers to strengthen their operations worldwide. Being global retailers, these multinational corporations have the ability to expand the sales of halal products produced in Malaysia to other countries through their subsidiary networks. If global retailers are quick to realize that halal products and concepts can be fully exploited to their advantage as what the banking industry had done with Islamic finance concepts, then they should be able to experience competitive advantage which is crucial in this day and age of the business world. However, MNCs themselves need to firstly realize and accept that adapting to host country’s culture can be a way of increasing their knowledge regarding various methods of operations.